The Urgency of Legal Reform for the Legality of Digital Currency in Indonesia - Agus Joko Lelono; Mohamad Tohari; Hono Sejati (LPPM Universitas Ekasakti Padang, 2024)
The purpose of this study is to explore the understanding and analyze the legal updates regarding the validity of money as a transaction tool in Indonesia and to understand and analyze the validity of electronic money used as an intermediary for electronic transactions. The method used in this study is normative legal research with a focus on legislation, applying qualitative descriptive data analysis techniques. The research results indicate that money serves several functions, including as a medium of exchange, store of value, unit of account, and deferred payment measure. The use of Indonesian Rupiah is regulated by several laws, including Emergency Law No. 20 of 1951, Currency Law, and Bank Indonesia Law. The validity of electronic money is regulated by Bank Indonesia Regulation No. 11/12/PBI/2009 concerning Electronic Money or Non-Cash Money (E-money). The purpose of this regulation is to encourage society to transition from using cash to non-cash or E-money. Electronic money is one type of non-cash payment instrument, along with paper-based payment instruments such as checks and promissory notes, as well as paperless payment instruments such as electronic fund transfers and card payments such as ATMs, credit cards, debit cards, and prepaid cards. These non-cash payments do not use physical money as a payment instrument but rely on innovations in electronic payments.